2D numerical study on flow boiling of zeotropic mixture isobutane/pentane in internal countercurrent flow system. (5th March 2017) - Zhang, Jianyuan; Wen, Jue; Deng, Shuai; Bao, Junjiang; Zhao, Li
Highlights: The flowing boiling of binary zeotropic mixture isobutane/pentane in internal countercurrent flow system is simulated. The evaporation model is validated with experimental data. Effective diffusion model is recommended. Abstract: Based on effective diffusion model and volume of fluid (VOF) model, the evaporation process of zeotropic mixture isobutane/pentane in an inclined straight flow channel is investigated. The physical properties of mixture and the source terms in the continuity, momentum, energy and species conservation equations are coded through User Defined Functions (UDF). The simulation results show that the evaporation rate first increases and then decreases from the entrance of vapor to the exit. The interaction of shearing force is relatively stronger at the top and bottom walls than that of near the interface. The velocity boundary layer is similar to the temperature boundary layer. The evaporation rate of pentane is higher than that of isobutane in the unit of kg/s because of its higher molecular weight. In addition, according to available experimental data, another physical model is built to validate the effective diffusion model. The mean absolute percentage error (MAPE) of heat transfer coefficient for all the four cases is 6.9%. This statistical indicator shows that the effective diffusion model proposed by Banerjee can reasonably describe the flow boiling of zeotropic mixture isobutane/pentane.